Estimation of the progenitor cell yield in a leukapheresis product by previous measurement of CD34+ cells in the peripheral blood - Möhle, Robert; Martin, Simona; Pförsich, Margit; Witt, Barbara; Haas, Rainer (Vox sanguinis, 1996)
To assess whether measurement of CD34+ cells in the peripheral blood allows one to estimate the progenitor cell yields of subsequent leukapheresis procedures, 733 corresponding blood and leukapheresis samples were analyzed. Peripheral blood progenitor cells of cancer patients were mobilized with hematopoietic growth factors alone or postchemotherapy, and harvested processing 10 liters of blood for each leukapheresis product. The CD34+ cell count (CD34+ cells/μl blood) correlated most closely with the progenitor cell yield in the corresponding leukapheresis product (CD34+ cells/kg bodyweight, r = 0.80), while the proportion of circulating CD34+ cells to the white blood and mononuclear cells predicted the yield less reliably (r = 0.74 and r = 0.60). The CD34+ cell yield was independent of the white blood count (r = 0.04), whereas a weak correlation was found between the mononuclear cell count and the number of CD34+ cells/kg collected (r = 0.42). It was unlikely to obtain the threshold quantity of 2.5 × 106 CD34+ cells/kg required for rapid engraftment when counts below 10 CD34+ cells/μl blood were detected. At levels between 10 and 30 CD34+ cells/μl sufficient autografts could be harvested, whereas 30-100 CD34+ cells/μl were required to achieve this by a single leukapheresis. A surplus of CD34+ cells was likely above 100 CD34+ cells/μl which could be useful for progenitor cell enrichment techniques. The correlation between the CD34+ cell count and progenitor cell yield was independent of the mobilizing regimen and whether leukaphereses had been performed previously. In conclusion, the number of CD34+ cells/μl blood allows a reliable prediction of the CD34+ progenitor cell yield in subsequent leukapheresis procedures. However, rare cases of unexpectedly sufficient progenitor cell yields may be observed even at CD34+ cell levels below detection limit.
Gesehen am 15.05.2025